Requests for assistance in the third-age language classroom. Issue 4 (2nd October 2022) - van der Ploeg, Mara; Willemsen, Annerose; Richter, Louisa; Keijzer, Merel; Koole, Tom
ABSTRACT: In this conversation analytic study, we investigate requests for assistance in the third-age (65+) language classroom. Seven Dutch seniors participated in a one-month course of English as a foreign language. We found that these seniors asked many language-related questions which fell into one of three categories: (1) production-oriented questions, (2) comprehension-oriented questions and (3) wonderment questions. These questions differ in the ways the sequences are shaped: (a) what precedes the request for assistance, (b) the person who is recruited to provide the assistance, (c) the person who offers the assistance, and (d) the response to the provided assistance and the subsequent interaction. We found wonderment questions to be the most prevalent category. Our findings suggest that the senior learners in our data show clear ownership and agency over their own learning process, demonstrated by their active participation and frequent (wonderment) questions in the classroom.